Effects of dietary rumen undegradable protein:rumen degradable protein ratio on nitrogen metabolism in Hanwoo steers - Sang Yeob Kim; Rajaraman Bharanidharan; Seyun Im; Kyoung Hoon Kim; Joonpyo Oh; Hyun Jin Kim; Jaesung Lee; Kamburawala Kankanamge Tharindu Namal Ranaweera; Jin Woo Jeong; Jun Seok Oh; Sang Hyun Lee; Myunggi Baik (Animal Bioscience)
Objective We investigated the effects of dietary rumen undegradable protein (RUP): rumen degradable protein (RDP) ratio on growth performance, nitrogen (N) metabolism, and rumen and blood parameters in Hanwoo (Korean cattle) steers. Methods Eight Hanwoo steers (average body weight, 393 kg) were allocated to two groups and fed with a high RUP:RDP ratio (46.9:53.1 based on crude protein) or a low RUP:RDP ratio (30.6:69.4) concentrate with iso-crude protein content in a 2×2 Latin square design in two successive periods. Results The high RUP:RDP group had higher (p<0.01) average daily gain, and lower (p<0.05) ruminal ammonia and plasma urea N concentrations than the low RUP:RDP group. The high RUP:RDP group had lower (p<0.05) urinary N excretion and urinary N per N intake and higher (p<0.1) tendency of retained N than the low RUP:RDP group. The high RUP:RDP group had higher (p<0.1) tendency of N utilization efficiency (retained N per N intake: 28.7% vs. 25.5%) than the low RUP:RDP group. The high RUP:RDP group had a lower (p<0.1) tendency of urinary N per total N excretion, but a higher tendency of fecal N per total N excretion. Conclusion A high ratio of dietary RUP:RDP may improve N utilization efficiency by reducing urinary N excretion, which may be beneficial for the environment through reducing atmospheric ammonia emissions.